Heavy Metals Analysis of Imported Scomber scombrus Sold by Cold-Rooms in Lagos State of Nigeria - Ogundele, Olusola D.; Okunade, Muda B.; Oyegoke, David A.; Olulana, Caroline O. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
This research aimed at assessing the heavy metals concentration in imported Scomber scombrus fish samples purchased from cold rooms in Lagos, Nigeria. The samples were digested using the wet digestion method, and the concentration of Chromium (Cr), Arsenic (As), Lead (Pb), and Cobalt (Co) were determined using Atomic Absorption Spectrophotometer. Chromium (Cr) was present in twelve Scomber scombrus samples, and the level ranged from 0.004 to 0.046 mg/kg, while arsenic (As) was present in seven fish samples, with concentrations varying within 0.001 to 0.006 mg/kg. Lead (Pb) was present in eleven samples and not detected in SS5 and SS7. The concentration ranged from 0.004 to 0.062 mg/kg. Cobalt (Co) was present in seven Scomber scombrus samples, the level ranged from 0.004 to 0.046 mg/kg. However, SS3, SS10, and SS13 had lead concentrations above the maximum permissible limit (0.05 mg/kg) recommended by WHO/FAO. This study established the need for Nigerian agencies in charge of food to verify, check and ascertain the safety of imported fish before endorsing them as harmless for citizens' consumption.